2020
DOI: 10.1017/cts.2020.36
|View full text |Cite
|
Sign up to set email alerts
|

Home care workers caring for adults with heart failure need better access to training and technology: A role for implementation science

Abstract: AbstractAlthough highly involved in heart failure (HF) patients’ care, home care workers (HCWs) lack HF training and are poorly integrated into the healthcare team. For its potential to address these challenges, we examined the role of technology among HCWs caring for HF patients. We conducted 38 interviews with key stakeholders. Overall, four themes emerged. Participants reported that technology is critical for HF care, but existing systems are outdated and ineffective. HCWs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…24 In light of this, previous research has highlighted the limited training that home care workers receive on heart failure symptoms and management. 12,[14][15][16] Given that heart failure has unique needs and disease trajectory and that home care workers' scope of care differs from that of family caregivers and healthcare providers, this study identified their educational needs and priorities as paid caregivers caring for heart failure patients at the end-of-life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In light of this, previous research has highlighted the limited training that home care workers receive on heart failure symptoms and management. 12,[14][15][16] Given that heart failure has unique needs and disease trajectory and that home care workers' scope of care differs from that of family caregivers and healthcare providers, this study identified their educational needs and priorities as paid caregivers caring for heart failure patients at the end-of-life.…”
Section: Discussionmentioning
confidence: 99%
“…13 A majority of home care workers do not receive systematic training on and feel ill-equipped to provide endof-life care for heart failure patients. 12,[14][15][16] States in the U.S. have invested funds towards the training and development of home health workers; however, limited research has explored their training needs. 17 To address this gap, we elicited the educational needs and priorities of home care workers caring for community-dwelling adults with heart failure at the end-of-life.…”
Section: Introductionmentioning
confidence: 99%
“…15,34,35 ICT implementation and adoption are key and beneficial to assist health care aides' workflows and activities. 36,37 Existing supporting health care tools can potentially provide a range of applications and platforms to facilitate health care aides' assignments, 38 transmit observations, and enhance communication between families, clients, and health care providers within the ecosystem of care. 39 ICT can help to deliver real-time support and keep clients' information confidential and available, 40,41 and ultimately improve caring activities and health care delivery.…”
Section: Background and Significancementioning
confidence: 99%
“…39 ICT can help to deliver real-time support and keep clients' information confidential and available, 40,41 and ultimately improve caring activities and health care delivery. 37 Despite the various technology-based interventions that exist, none have been designed with health care aides in mind or intended to support their workflows. 37 For example, Steele Gray et al 42 found that ICT for health care aides are inefficient and often do not fit their workflows.…”
Section: Background and Significancementioning
confidence: 99%
“…Eder at al. 13 describe practice facilitation as an important implementation strategy to communicate shared project goals and monitor practice behaviors, while Sterling et al, 15 examine the role of a specific group of neglected stakeholdershome care workers. Fiscella et al 16 discussed the role of data and safety monitoring boards (DSMBs) in implementations trials, raising the question about whether monitoring for differences in effectiveness is necessary or appropriate, and whether additional systems-level implementation outcomes should be monitored, such as impact on workflow and workforce that could create strain on the staff or increase access to care barriers.…”
Section: Broad Themes From Papers Published In This Jcts Special Issumentioning
confidence: 99%